Validity of a device designed to measure braking power in bicycle disc brakes - Miller, M. C.; Fink, P. W.; Macdermid, P. W.; Perry, B. G.; Stannard, S. R. (Sports Biomechanics, 2018)
Real-world cycling performance depends not only on exercise capacities, but also on efficiently traversing the bicycle through the terrain. The aim of this study was to determine if it was possible to quantify the braking done by a cyclist in the field. One cyclist performed 408 braking trials (348 on a flat road; 60 on a flat dirt path) over 5 days on a bicycle fitted with brake torque and angular velocity sensors to measure brake power. Based on Newtonian physics, the sum of brake work, aerodynamic drag and rolling resistance was compared with the change in kinetic energy in each braking event. Strong linear relationships between the total energy removed from the bicycle-rider system through braking and the change in kinetic energy were observed on the tar-sealed road (r2 = 0.989; p < 0.0001) and the dirt path (r2 = 0.952; p < 0.0001). T-tests revealed no difference between the total energy removed and the change in kinetic energy on the road (p = 0.715) or dirt (p = 0.128). This study highlights that brake torque and angular velocity sensors are valid for calculating brake power on the disc brakes of a bicycle in field conditions. Such a device may be useful for investigating cyclists` ability to traverse through various terrains. ABSTRACT FROM AUTHOR